Immunoprotective effects of extracellular products of Pasteurella multocida on mice - Li, Jingtao; Liu, Wan; Zhang, Xiaoyu; Song, Yang; Chen, Li; Shi, Qiumei; Wu, Tonglei (Frontiers in Microbiology, 2025)
BackgroundPasteurella multocida (P. multocida) is a globally significant pathogen causing severe infections in livestock, including hemorrhagic septicemia and respiratory diseases. Current vaccines offer limited serotype-specific protection, particularly against serotype A:3, a major cause of bovine respiratory disease. Extracellular products (ECPs) of bacteria, containing secreted proteins and enzymes, have shown promise as immunogens in other pathogens, but their potential against P. multocida remains unclear.MethodsExtracellular products were isolated from P. multocida serotype A:3 strain PmQA-1 and characterized via SDS-PAGE, mass spectrometry, and enzymatic activity assays. Pathogenicity was evaluated by determining the median lethal dose (LD50) in mice. Mice were immunized with ECPs, formalin-killed cells (FKC), or a combination (FKC + ECPs), and immune responses (serum IgG, splenic lymphocyte proliferation, cytokine expression) were assessed over 28 days. Protective efficacy was tested via challenge with homologous (A:3) and heterologous (B:2, D:4) strains.ResultsExtracellular products contained 157 proteins (25–100 kDa), including immunogenic factors like transferrin-binding protein A, and exhibited stable amylase activity. The LD50 of ECPs in mice was 2.69 mg/mouse, inducing lesions typical of P. multocida infection. ECP-immunized mice showed peak IgG levels at day 21, enhanced lymphocyte proliferation, and upregulated TNF-α, IFN-γ, IL-1β, and IL-10 in key tissues. Challenge experiments demonstrated 100% survival against A:3 and B:2, and 90% against D:4, outperforming FKC and FKC + ECPs.ConclusionExtracellular products from P. multocida serotype A:3 induce robust humoral and cellular immunity, providing broad-spectrum protection against multiple serotypes. These findings support ECPs as a promising subunit vaccine candidate for controlling P. multocida infections in livestock.